Mohammad Taghi Qiasi and Translation of French Poetry - Mitra Raissi Dehkordi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Mohammad Taghi Qiasi has been researching in different fields of French language and literature. In addition, he has provided numerous translations from French to Farsi, particularly about the translation French works. Among his translations, two books are dedicated to the translation of French poetry. Initially, the translation of forty four pieces of Paul Eluard’s poems entitled Oh Freedom by Mohammad Taghi Qiasi was published in 1978. Later, French Poetry in Twentieth Century was published by Nahid Publications. However, the reasons for the inclusion of some nineteenth century poems have been explained in the introduction of the book. In fact, the French poetry has been only sparsely translated into Persian language, and therefore, it has got a different course in comparison to French prose works. In this way, those who adore poetry have not got the opportunity to get familiar with the rich and influential French poetry. In the present paper, we review the book of French Poetry in the Twentieth Century. We aimed to analyze the reasons for the selection of poems, the method for the introduction of poets, and the classification of the history of French poetry to different periods, as well as the translation methods. In this review work, we aimed to demonstrate to which extent this book may aid those who adore literature, to get familiar with the French poetry